ВИВЧЕННЯ ПРОТИВІРУСНОЇ АКТИВНОСТІ ТАБЛЕТОК АЛЬТАБОР - Рибалко, С. Л.; Крутських, Т. В.; Шаламай, А. С. (Фармацевтичний часопис, 2015)
STUDY OF ANTIVIRAL ACTIVITY OF TABLETS ALTABOR S.L. Rybalko1, Т.V. Кrutskikh2, А.S. Shalamay3 1L.V.Gromashevsky Institute of epidemiology and infectious diseases Academy of Medical Science of Ukraine, Kyiv 2National Pharmaceutical University, Kharkiv 3JSC SIC "Borshchahivka CPP", Kyiv Summary: studied antiviral activity of tablets Altabor. Determined that the drug has antiviral activity and inhibits the reproduction of Epstein-Barr virus. Key words: altabor, antiviral activity, influenza, Epstein-Barr virus. Introduction. Among all infectious diseases flu and SARS took first place in frequency and the number of cases in the world and account for 95%. According to WHO influenza and flu-like illness in the world is sick 5 - 30 % of the population is 500 million people. For 400 years the world's recorded over 100 epidemics of influenza pandemics and 18, which bring it with them tens of millions of lives. Today, global losses from influenza epidemics is much inferior to the scale of past pandemics due to the possibilities of modern diagnosis of the virus , the availability of antiviral and antibacterial drugs and improving health services. But the problem of treatment of disease really matter remains relevant. Against the background of acute viral infections of herpes viruses can be said not, but no less threatening. Herpes was first fixed in a thousand years BC, but the problem that attracts attention, was only in the 20th century after the emergence of HIV. Today open 80 more members of the family of herpes viruses, of which 8 types pathogenic to man. One of the pathogenic types are Epstein-Barr virus, which, according to research antibodies detected in 95% of the population. At this time this virus play an important role in the formation of cancer cells in the body that causes the need for increasing attention from the medical and pharmaceutical community. Create antiviral agents is one of the most difficult tasks chemotherapy infections. The reason is that viruses containing RNA and DNA components are obligate intracellular parasites. In the process of viral replication is mainly used machine biosynthesis microorganism cells, modifying its outstanding manner. In this regard, it is very difficult to find selective operating means which would killed viruses without damaging the cells are "master". However, in recent years, certain antiviral drugs that possess outstanding selective action against the infected cells and suppress the virus replicative cycle. One of these drugs is original domestic product - Altabor tablets. Methods. Antiviral activity of Altabor tablets studied in models in vitro. To determine influenza activity using dog kidney cell culture .The influence of tablets Altabor on virus Epstein-Barr conducted in the system Raji cells infected with the said virus. Results and discussion. Altabor tablets influenza activity based on the inhibition of viral neuraminidase, an enzyme responsible for viral virion ability to penetrate the host cell and leave it after reproduction. Analyzing these data, it should be noted that tablets Altabor actively inhibit the reproduction of the influenza virus in doses from 100 mg/ml to 6.75 ug/ml 7.5-3.0 lg ID50, which indicates a strong flu drug activity. As for the study of the effect of tablets on Altabor Epstein-Barr virus, the maximum tolerated concentration was 750 mg/ml. Determined that the minimum active concentration for the drug was 0.1 mg/ml. Based on the value of the minimum and maximum tolerated concentration of active therapeutic index of tablets Altabor established at 5000, indicating a pronounced effects on reproduction of the virus. Conclusions. Result of studies on the antiviral activity of tablets Altabor found that the preparation has flu activity. Also, the drug inhibits the reproduction of Epstein-Barr virus, as evidenced therapeutic index of tablets Altabor set at 5000.